Effects of partial substitution of Cu for Co on the microstructure and properties of WC-Co-Mo cemented carbides. Issue 10 (15th May 2021) - Wang, Yanliang; Liu, Wenjuan; Zhong, Chaofa; Wu, Jian; Ye, Y.W.
Abstract: In this work, Co–Cu metals were used as binder phase of cemented carbides. The influence of Cu content (0.8, 1.2, 1.6, and 2.0 wt%) on microstructure and properties of WC-Co-Cu-Mo alloys was discussed compared with WC-Co and WC-Co-Mo alloys. The results showed that the relative density, hardness, and transverse rupture strength of WC-Co alloys were significantly improved, and the WC average size, wear rate and corrosion resistance were greatly decreased by adding 1.2 wt% Cu. Among them, the hardness and density of WC-Co alloy increased from 1713 HV30 and 98.83% to 1908 HV30 and 99.31%, respectively. The average WC grain size and the corrosion rate of WC-Co alloy under HCl solution decreased from 0.68 μm and 303.23 μA cm −2 to 0.53 μm and 27.32 μA cm −2, respectively. These phenomena indicated that the doping of proper Cu into WC-Co-Mo alloys could enhance the comprehensive performance of WC-Co alloy.